Young Children’s Full-Day Patterns of Cortisol Production on Child Care Days - Sumner, Melissa Manni (2010)
OBJECTIVE: To examine toddlers’ full-day patterns of cortisol production on child care days and non–child care days, with a particular focus on whether the mid-afternoon elevations at child care persist into the evening or decrease to typical levels observed on non–child care days. DESIGN: A prospective observational study. SETTING: Four child care centers in a suburban, mid-Atlantic area. PARTICIPANTS: Forty-two children aged 16 to 24 months attending full-day child care. MAIN EXPOSURE: Full-day child care. OUTCOME MEASURE: Salivary cortisol samples obtained at wake-up, mid-morning, mid-afternoon, and bedtime for children on 2 child care days and 2 non–child care days. RESULTS: Children showed different patterns of cortisol production on child care days compared with non–child care days ([Formula: see text] , P=.001). Child care days were characterized by an afternoon increase in cortisol levels (unlike non–child care days) and decreases to bedtime values that were comparable with levels on non–child care days. CONCLUSION: Results suggest that the effects of child care on children’s cortisol production are time limited across the day.